The Early Iron Age Fort at Lizq, Sultanate of Oman - Kroll, Stephan (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
Shaikh Hamdan al-Harthy brought Gerd Weisgerber to the Gabal Radhaniya in 1979 – the largest Early Iron Age fort in south-eastern Arabia. A single season of excavation followed in 1981. Kroll finished an excavation report in 1982 but the publication was postponed. Important at this time is Kroll’s comparison of the pottery from Lizq with that of Iran of the late 2nd and 1st millennia B. C. E. The Lizq fort owes its existence to the reliable occurrence of water at a natural causeway at the southern side of the central mountains. The main fort on the western mountain peak is some 175 m wide and had a surface of more than 20 000 m². The location of the village associated with the fort remains unknown. Another fort located 4 km north of Bisyah village also dates to the Early Iron Age and shares certain similarities. The article will be available as a PDF in the near future.